2008
DOI: 10.1182/blood-2007-12-127183
|View full text |Cite
|
Sign up to set email alerts
|

Expression, activation, and function of integrin αMβ2 (Mac-1) on neutrophil-derived microparticles

Abstract: IntroductionLeukocyte-platelet cross-talk plays multiple and important roles in inflammatory and thrombotic responses. 1 Activated platelets and platelet-released mediators, such as PDGF and PAF, activate leukocytes enhancing their responses such as adhesion, chemotaxis, phagocytosis, and superoxide generation. [2][3][4][5] Conversely, activated leukocytes induce platelet activation as evidenced by increased platelet P-selectin expression. 6 In vivo studies show that leukocytes and platelets colocalize within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 74 publications
5
148
1
7
Order By: Relevance
“…95 According to a recently published study, leukocyte-derived microparticles also act as a novel platelet agonist targeting GPIba, a platelet-adhesion receptor important for initiation of clot formation by binding von Willebrand factor (vWF); such leukocyte-platelet interactions are amplified in situation when neutrophils are also activated. 95,96 It is important to note the link between vWF, endothelial injury, and cGVHD described by Biedermann et al 97 They found that cGVHD patients have extensive loss of microvessels in affected tissues and increased circulating vWF concentrations, concluding that vWF was released from vascular endothelial cells injured in process of cGVHD. 97 In summary, involvement of microparticles formation in coagulation, inflammation, and vascular problems, as well as in other platelet-leukocyte-endothelial processes and interactions, 98 could have important roles in the pathophysiology of tissue damage found in cGVHD.…”
Section: Microparticlesmentioning
confidence: 97%
“…95 According to a recently published study, leukocyte-derived microparticles also act as a novel platelet agonist targeting GPIba, a platelet-adhesion receptor important for initiation of clot formation by binding von Willebrand factor (vWF); such leukocyte-platelet interactions are amplified in situation when neutrophils are also activated. 95,96 It is important to note the link between vWF, endothelial injury, and cGVHD described by Biedermann et al 97 They found that cGVHD patients have extensive loss of microvessels in affected tissues and increased circulating vWF concentrations, concluding that vWF was released from vascular endothelial cells injured in process of cGVHD. 97 In summary, involvement of microparticles formation in coagulation, inflammation, and vascular problems, as well as in other platelet-leukocyte-endothelial processes and interactions, 98 could have important roles in the pathophysiology of tissue damage found in cGVHD.…”
Section: Microparticlesmentioning
confidence: 97%
“…In another study, stimulation of neutrophils with bacterial endotoxin resulted in shedding of PAF containing microparticles which activated platelets [118]. More recently, the active form of the β2 integrin Mac-1was detected on the surface of EVs released from activated neutrophils, and the active integrin played a central role in binding to and activation of resting platelets [84].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 97%
“…Microvesicles shed from neurons and astrocytes contain growth factors and promote paracrine responses (Proia et al, 2008;Schiera et al, 2007). In addition, membrane proteins on microvesicles have been shown to interact specifically with molecules on target cells to promote signaling responses (Eken et al, 2008;Gasser et al, 2003;Losche et al, 2004;Pluskota et al, 2008). In some cases, direct binding results in fusion of the microvesicle with the target cell or endocytosis of the microvesicle.…”
Section: Introductionmentioning
confidence: 99%